Comprehensive evaluation of stormwater pollutants characteristics, purification process and environmental impact after low impact development practices. (1st January 2021) - Kong, Zheng; Shao, Zhiyu; Shen, Yue; Zhang, Xiaodan; Chen, Mingyan; Yuan, Yunsong; Li, Guo; Wei, Yingyan; Hu, Xuebin; Huang, Yuming; He, Qiang; Chai, Hongxiang
Abstract: Understanding the stormwater characteristics and purification process of different underlying surfaces in an intensive Low Impact Development (LID) catchment is critical for summarizing problems of built LID practices and providing references for future LID construction. This research program investigated stormwater pollutants from several sites in Yuelai, Chongqing, a pilot area of Chinese Sponge Cities. The results showed that different LID areas had different stormwater pollutant characteristics and purification processes due to different LID layouts and facilities. For highway runoff, pollutants event mean concentrations (EMCs) were mainly affected by rainfall characteristics rather than road slopes. Ammonia was the primary nitrogen pollutant, and it always has a heavier first flush effect (FFE). For the green parks, runoff volume and FFE reduction were effective because of the high density of soil-based LID facilities and natural green space. However, nitrate and organic matter leaching also existed. The commercial areas often have more engineering facilities which could remove solids pollutant and phosphorus effectively. However, nitrogen removal performance was poor. The residential areas compromised between green parks and commercial areas. Overall, LID construction significantly reduced pollutants EMCs, volume and FFE, ameliorated water quality of the receiving water bodies. Nevertheless, some problems, such as inadequate nitrogen removal and runoff scouring effect, still need to be resolved in the future. Graphical abstract: Image 1 Highlights: Urban stormwater runoff of 4 LID sites was studied. LID decreased pollutant concentration and first flush effect. Pollutant purification process varied between different LID sites. River water quality improved after LID construction. Nitrogen is the main stormwater pollutant.